Cultural characteristics of Crumenula sororia - Hayes, A. J.; Ahmad, Abdul Manap (British Mycological Society, Elsevier, 1975)
As agar cultures of most Crumenula sororia Karst, isolates aged, the initially grey coloration darkened to olivaceous black with the development of a central umbo and a lighter fringe. Some isolates produced a copious exudate that diffused into the substrate. Optimum growth occurred in the temperature range 15–22·5°. As temperatures increased, all cultures were affected similarly, but as temperatures decreased isolate differences occurred, those from Pitmedden and the Netherlands being more severely restricted. The isolate from Pitmedden grew equally well in light and dark conditions, but those from Ringwood, Bramshill, Hallyburton and the Netherlands were favoured by darkness. With both solid and liquid media, growth was maximal in the pH range 4·0–7·0. C. sororia grew better on malt media than on those consisting of potato dextrose, Czapek Dox, Yeast extract or nutrient broth. The fungus usually produced submerged, opaque non-pigmented hyphae in liquid media excepting those with malt or yeast where hyphae were mainly aerial and darkly pigmented. Best growth of C. sororia on solid media occurred when ammonium nitrate was supplied as the nitrogen source, whereas in liquid media asparagine or glutamic acid were superior to any inorganic source. Maltose and lactose were not so readily assimilated as other carbohydrates. In solid media the optimum concentration of sucrose for growth was 10% whereas in liquid culture a positive response to 20 % sucrose was obtained. Growth of C. sororia in culture was stimulated by wood and bark extracts of Corsican pine, one of the host species of the fungus. Good growth of C. sororia was generally biotin dependent.